Enhanced “Green Nudging”: Tapping the channels of cultural transmission - Christian Cordes; Joshua Henkel (PLoS ONE, 2025)
This paper shows how to increase the effectiveness of “green nudging” as a policy measure to induce sustainable preferences. Evidence indicates that the behavioral impact of “green nudges” is subject to decay. To address this problem, we propose “enhanced green nudges”, which incorporate learning biases as features of humans’ capacity for culture. These provide information for the formation of enduring “green” preferences. Several biases in cultural transmission are considered, such as direct bias, norm-following behavior, conformity, self-similarity, and the influence of role models. Moreover, a prerequisite for “enhanced green nudges” to be effective is that learning environments resemble the ones biases evolved from in humans’ evolutionary past. Based on a model of cultural evolution, several scenarios of preference acquisition through “green nudges” illustrate our arguments and indicate implications for policy.